A nyilvánosság elvének érvényesülése a büntetőeljárásban - Varga, Petra (Debreceni Jogi Műhely, 2018)
Publicity, as a key principle of the criminal procedures, has been one of the major topics of the criminal procedure reform-movements since the 18th century. Publicity is a safeguard which guarantees the indepence and impartiality of the court and it is also a significant instrument of social control. In the Hungarian legal system, regulations concerning publicity are located on multiple levels, which means they are not integrated. This kind of disintegrationen dangers the legal certainty. This study introduces the legal practice of the European Court of Human Rights (ECHR) concerning publicity and also detail show this principle appears in the constitutions of various European countries. Furthermore it examines the relevant legislations in force and the new Criminal Procedure Statute, which will come into force on 1st of July, 2018. Finally, the study mentions some de lege ferenda recommendations, in order to support the future legal-developing actions